2018
DOI: 10.1111/echo.13899
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of left atrial mechanical dispersion over CHA2DS2VASc score in predicting risk of thrombus formation

Abstract: Left ventricular systolic dysfunction characterized by both LVEF and LVGLS is an independent factor for LAAT. LA asynchrony provides additional diagnostic value for discriminating between patients with and without LAAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Kupczynska et al [28] have demonstrated the value of speckle-tracking analysis of the LA wall to identify patients with higher risk of thrombus. Additionally, both LVEF and global longitudinal turned out to be an independent risk factor for thrombus and provided additional diagnostic value for discriminating between patients with and without left atrial thrombus [29]. One of the most relevant and clinically important findings of the study is the relationship between cognitive dysfunction and thrombus (Figs.…”
Section: Discussionmentioning
confidence: 86%
“…Kupczynska et al [28] have demonstrated the value of speckle-tracking analysis of the LA wall to identify patients with higher risk of thrombus. Additionally, both LVEF and global longitudinal turned out to be an independent risk factor for thrombus and provided additional diagnostic value for discriminating between patients with and without left atrial thrombus [29]. One of the most relevant and clinically important findings of the study is the relationship between cognitive dysfunction and thrombus (Figs.…”
Section: Discussionmentioning
confidence: 86%
“…It remains to be seen if the “appealing” biomarker in the form of LA strain and its dispersion can offer yet another opportunity to benefit patients with AF. Kupczynska et al have given us a compelling optimism in that direction, as we are lost in the vicious cycle of atrial myocardial disarray and atrial fibrosis that have inverse relationship with reservoir strain and are substrates for perpetuation of atrial fibrillation …”
Section: Resultsmentioning
confidence: 99%
“…In their excellent work published in this issue of the Journal, Kupczynska and colleagues investigated ninety‐three patients that were referred for routine transesophageal echocardiography for clinical indications such as direct current cardioversion for symptomatic and eligible subjects with AF. The investigators have not only studied absolute LA strain but also dispersion of LA strain with excellent reproducibility.…”
Section: Left Atrial Strain As a Biomarker In Atrial Fibrillation?mentioning
confidence: 99%
See 2 more Smart Citations